Design, Synthesis and Preliminary Pharmacological Evaluation of Mutual Prodrug of Non-Steroidal Anti-Inflammatory Drugs Coupling With Natural Anti-Oxidants Via Glycine - Monther Faisal Mahdi; Ashour H. Dawood; Ahmed Kareem Hussein (College of Pharmacy / Mustansiriyah University, 2013)
Non-steroidal anti-inflammatory drugs (NSAIDs); naproxen and indomethacin have been conjugated with different antioxidants (thymol, menthol & guaiacol) having antiulcerogenic activity via glycine amino acid as spacer with the objective of obtaining NSAIDs-glycine- antioxidant prodrugs as gastrosparing NSAIDs devoid of ulcerogenic side effects and synergistically with anti-inflammatory action of glycine. Four mutual prodrugs (IIV) were synthesized using glycine as spacer and their structures were confirmed and characterized using elemental microanalysis (CHNO), IR, and some physiochemical properties. Invivo acute anti-inflammatory activity of the compounds (I & II) (naproxen derivatives) and the compounds (III & IV) (indomethacin derivatives) was evaluated in rat using an egg-white induced edema model of inflammation in a dose equivalent to 2.5 mg/Kg of naproxen, and 2 mg/Kg of indomethacin respectively. All tested compounds produced significant reduction of paw edema with respect to the effect of propylene glycol 50% v/v (control group). Moreover, the activity of compound III was significantly higher than that of indomethacin (at 2 mg/Kg), while compound IV expressed a comparable effect to that of indomethacin in the (120-300) minute time of the experiment, while compounds I&II was showed a comparable effect to that of naproxen at (180-300) minute time interval of the experiment. The result of this study indicates that these mutual prodrugs of naproxen & indomethacin maintained or may enhanced their antiinflammatory activity.